2023
DOI: 10.3389/fcvm.2023.1082725
|View full text |Cite
|
Sign up to set email alerts
|

There is more than just longitudinal strain: Prognostic significance of biventricular circumferential mechanics

Abstract: IntroductionDespite the significant contribution of circumferential shortening to the global ventricular function, data are scarce concerning its prognostic value on long-term mortality. Accordingly, our study aimed to assess both left (LV) and right ventricular (RV) global longitudinal (GLS) and global circumferential strain (GCS) using three-dimensional echocardiography (3DE) to determine their prognostic importance.MethodsThree hundred fifty-seven patients with a wide variety of left-sided cardiac diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Kaplan-Meier analysis showed that median values of 3D RV GCS, GLS and GAS stratified these patients by survival rates 21 . Tolvaj et al have described the association between reduced RV GCS and significantly increased risk of mortality, even in scenarios where LV GLS is preserved 22 .…”
Section: Evidence About the Clinical Utility Of The Different Compone...mentioning
confidence: 99%
“…Kaplan-Meier analysis showed that median values of 3D RV GCS, GLS and GAS stratified these patients by survival rates 21 . Tolvaj et al have described the association between reduced RV GCS and significantly increased risk of mortality, even in scenarios where LV GLS is preserved 22 .…”
Section: Evidence About the Clinical Utility Of The Different Compone...mentioning
confidence: 99%